(untitled) - Bharal, Dr. Chavvi (India, 2006)
The Dictionary of Environmental Science and Engineering is an essential reference book for students and professionals in such diverse disciplines as geography, earth sciences, biology, engineering and law. Expanded from its original publication, this comprehensive and concise guide defines the scientific and the technical terminology that surrounds this high profile topic
Anh văn chuyên ngành
Keywords: Environmental engineering,Quản trị môi trường; Dictionaries,Từ điển